A formação do pedagogo-professor no curso de pedagogia: limites e possibilidades na visão de professores formados no campus avançado de Patu da UERN - Melo, Jacicleide Ferreira Targino da Cruz (2010)
The inconclusive policies regarding the teaching background, specifically the Pedagogy Course, whose National Curricular Directives DCN were ratified by the Ministry of Education on April 4th 2006, have been causing protest from the various forces within the scope of the university, specifically in the Pedagogy Departments in which, through their professionals, express the several stands about the pedagogue profile, his/her professional acting field and a curriculum that meets the background needs of this professional. This paper tried to assess, from the viewpoint of the student who graduated from the Pedagogy Course and who acts in classroom in the first years of the Elementary School, to what extent this course meets the background needs of the professional who works as teacher. In specific terms it was this paper's objective to identify the most important background needs of teachers who graduated in Pedagogy, who act in the first years of the Elementary School; To list the contributions and limitations of the Pedagogy Course of CAJIM/UERN in the teachers' background, outlined by the graduates of the course; to raise suggestions for the improvement of the teachers' background in the Pedagogy Course of the CAJIM/UERN. In order to turn these objectives viable we opted for the qualitative approach in research, more precisely for the case study methodology, from which we used as instruments for the execution of the field work the observation in classrooms, semi-structured interviews which became the main instrument used for the data construction and analysis. The data analysis process took place through the content analysis technique based in Bardin (2000). The theoretical line is based on the studies from Schön (2000), Nóvoa (1997), Perrenoud (1993), Alarcão (2003), Ramalho (2003) we also used the National Curricular Directives which serve as current Parameter for the Pedagogy courses. The study indicated that the Pedagogy Course contributed for the personal and professional enrichment, however, difficulties in the theory-practice articulation are still present in the everyday life. The theoretical knowledge assimilated, though represent increments to the professional practice, are not enough to enable a pedagogical practice with excellence. There is a need to consider a curriculum in a dialectic perspective, configurator of social and cultural practices sustained by the reasoning as praxis, thus it must not be seen solely in a theoretical plan, mas as a process that builds itself between the acting and the reasoning.